Mirikizumab: A promising breakthrough in Crohn's disease treatment - Muaaz Aslam; Mohammad Haris Ali; Hamza Irfan (Health Science Reports)
Abstract Introduction Crohn's disease (CD) is a chronic, progressive inflammatory bowel disorder characterized by persistent inflammation and noncontiguous “skip lesions” throughout the gastrointestinal tract. With a prevalence of 100–300 cases per 100,000 individuals, CD is most common in Western Europe and North America. Symptoms include abdominal pain, diarrhea, fever, weight loss, and anemia, with severe cases leading to complications such as perianal abscesses and cutaneous fistulas. Treatment involves pharmaceutical interventions, bowel rest, and sometimes surgery, with biological therapies like ustekinumab and mirikizumab gaining prominence. Clinical Trials The VIVID‐1 trial assessed mirikizumab in patients with moderately to severely active CD. By Week 12, mirikizumab significantly outperformed placebo in clinical response (45.4% vs. 19.6%, p < 0.000001). By Week 52, it showed higher clinical remission rates (54.1% vs. 19.6%) and demonstrated non‐inferiority to ustekinumab in clinical remission (p = 0.51). The SEQUENCE study compared risankizumab to ustekinumab, with risankizumab showing superior reductions in inflammatory markers and higher biologic remission rates at Weeks 8, 24, and 48. Both treatments had similar safety profiles, with common adverse events including COVID‐19, anemia, and headache. Conclusion Mirikizumab, based on the VIVID‐1 trial outcomes, is a promising addition to CD therapy. It demonstrated significant clinical responses and remission rates, warranting further research on its long‐term efficacy and safety. Updating professional guidelines and addressing affordability will ensure broader access and improved management of CD.